Surface structure for enhancing condensation heat transfer as well as preparation method and application of surface structure

By combining the mesh structure layer and the wedge-shaped gradient channel structure layer on the condensation surface and forming a nanostructure layer and a hydrophobic coating, the problems of condensate overflow and pining are solved, and the condensation heat transfer efficiency and performance are significantly improved.

CN119713965AActive Publication Date: 2025-03-28HUAZHONG UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411902171.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

In the prior art, the thermal resistance of heat transfer caused by condensate droplet pinning and condensate overflow increases, and the condensation heat transfer efficiency and performance need to be improved.

Method used

A surface structure that strengthens condensation heat transfer is adopted, combining a mesh structure layer and a wedge-shaped gradient channel structure layer, and a nanostructure layer and a hydrophobic coating are formed on the surface to limit the overflow of the condensate and promote the downward transport of the liquid film.

Benefits of technology

It effectively limits the overflow and pinning of the condensate, improves the condensation heat transfer efficiency and performance, and achieves efficient drop-membrane condensation heat transfer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119713965A_ABST
    Figure CN119713965A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of heat transfer, and relates to a surface structure for strengthening condensation heat transfer and a preparation method and application thereof, and the surface structure sequentially comprises a net structure layer and a wedge-shaped gradient channel structure layer from top to bottom; the wedge-shaped gradient channel structure layer comprises wedge-shaped fins and wedge-shaped channels, and the wedge-shaped fins and the wedge-shaped channels are sequentially and adjacently arranged at intervals; the net-shaped structure layer is in contact with the wedge-shaped fins; the mesh diameter of the net-shaped structure layer is smaller than the channel width of the wedge-shaped gradient channel structure layer, the surfaces of the net-shaped structure layer and the wedge-shaped gradient channel structure layer are covered with nano-structure layers, and the nano-structure layers are covered with hydrophobic coatings. The invention can achieve the technical effects of limiting the formation of pinning liquid drops and the overflow of surface condensate, realizing reasonable separation of gas-liquid channels and improving the heat transfer efficiency and heat transfer performance of condensation, and can be widely applied to a condensation heat exchanger or a steam cavity condensation end or the enhanced condensation of seawater desalination collected water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of heat transfer technology, and in particular, relates to a surface structure for enhancing condensation heat transfer and a preparation method and application thereof. Background Art

[0002] With the continuous development of industrial fields such as seawater desalination, power generation, and air conditioning, each related equipment requires higher heat exchange efficiency. Condensation, as an efficient phase change heat transfer method, is one of the main heat transfer methods in the above-mentioned industrial fields. Therefore, improving the condensation heat transfer efficiency, reducing energy consumption, and accelerating the integration and efficiency of energy systems have become one of the main goals of technological improvements in various industrial fields.

[0003] The wettability and structural morphology of the heat exchange surface are key factors affecting the condensation heat transfer characteristics. The use of micro-nanostructured surfaces to regulate the behavior of droplets / liquid films can significantly enhance condensation heat transfer. In recent years, many scholars have developed many types of micro-nanostructured surfaces and coating surfaces to accelerate the detachment of droplets and improve the condensation heat transfer performance by changing the surface structure and wetting characteristics. At present, fins or grooved surfaces are often used to increase the condensation area and promote the sliding detachment of droplets, but the grooves are mostly straight rectangular grooves. The regulating effect of such grooves on droplets / liquid films is relatively simple and limited, and the removal efficiency of condensate on the surface needs to be improved. Furthermore, the super-hydrophobic groove surface combined with the micro-nanostructure is prone to droplet pinning and condensate overflow at high supercooling degrees, resulting in increased surface heat transfer thermal resistance and deterioration of condensation heat transfer.

[0004] Therefore, how to prepare a surface structure to limit the formation of pinned droplets and the overflow of surface condensate, and improve the heat transfer efficiency and heat transfer performance of condensation, has become a technical problem that needs to be solved urgently by technical personnel in this field. Summary of the invention

[0005] In view of the defects of the prior art, the present invention provides a surface structure for enhancing condensation heat transfer and a preparation method and application thereof, so as to solve the technical problems of increased heat exchange thermal resistance and deteriorated condensation heat transfer caused by condensation droplet pinning and condensation liquid overflow in the prior art, so as to achieve the technical effect of limiting the formation of pinned droplets and surface condensation liquid overflow, realizing reasonable separation of gas-liquid channels, and improving the heat transfer efficiency and heat transfer performance of condensation.

[0006] According to a first aspect of the present invention, a surface structure for enhancing condensation heat transfer is provided, which comprises, from top to bottom, a mesh structure layer and a wedge-shaped gradient channel structure layer; the wedge-shaped gradient channel structure layer comprises wedge-shaped fins and wedge-shaped grooves, and the wedge-shaped fins and the wedge-shaped grooves are arranged adjacent to each other in sequence; the mesh structure layer is in contact with the wedge-shaped fins; the mesh diameter of the mesh structure layer is smaller than the channel width of the wedge-shaped gradient channel structure layer, and the surfaces of the mesh structure layer and the wedge-shaped gradient channel structure layer are both covered with a nanostructure layer, and the nanostructure layer is covered with a hydrophobic coating.

[0007] Preferably, the structure of the wedge-shaped fin is a fin structure with a wedge-shaped gradient gradually contracting, and the structure of the wedge-shaped slot is a slot structure with a wedge-shaped gradient gradually expanding.

[0008] Preferably, the mesh diameter of the mesh structure layer is 10 μm to 100 μm, the mesh width of the mesh structure layer is 10 μm to 80 μm, and the mesh number of the mesh structure layer is 100 to 250 meshes.

[0009] Preferably, the widths of the wedge-shaped fin structure and the wedge-shaped groove structure are independently selected from 0.2 mm to 1.4 mm, and the depth of the wedge-shaped groove structure is 0.2 mm to 1 mm.

[0010] Preferably, the material of the mesh structure layer and the wedge-shaped gradient channel structure layer is selected from copper, aluminum and titanium.

[0011] Preferably, the material of the nanostructure layer is one or more of copper oxide, aluminum oxide, titanium oxide, and silicon oxide, and the material of the hydrophobic coating is one or more of thiol, fluorosilane, polytetrafluoroethylene, polydimethylsiloxane, paraffin, or carbon nanotubes.

[0012] According to another aspect of the present invention, a method for preparing the surface structure for enhancing condensation heat transfer is provided.

[0013] (1) making a mesh structure layer;

[0014] (2) selecting a substrate, and manufacturing a wedge-shaped gradient channel structure on the surface of the substrate to form a wedge-shaped gradient channel structure layer;

[0015] (3) The mesh structure layer is covered on the wedge-shaped gradient channel of the wedge-shaped gradient channel structure layer to form a combined body.

[0016] (4) immersing the combined body in an alkaline solution or an oxidizing solution that can oxidize the surface of the combined body to form a nano-metal oxide, thereby forming a nano-structured layer on the surface of the combined body by a chemical oxidation method;

[0017] or coating a suspension of a material containing a nanostructure layer on the combined body by a coating method to form a nanostructure layer on the surface of the combined body;

[0018] (5) Immersing the combined body having the nanostructure layer in a solution containing a hydrophobic molecular precursor, and forming a hydrophobic coating on the nanostructure layer by a molecular self-assembly method or a physical deposition method.

[0019] Preferably, the alkaline solution is selected from a mixed aqueous solution of NaClO2, NaOH and Na3PO4 or ammonia solution; the oxidizing solution is selected from a H2O2 solution, or a mixed aqueous solution of K2S2O8 and KOH, or a mixed aqueous solution of (NH4)2S2O8 and NaOH;

[0020] Preferably, a pretreatment step is further included before step (3), and the pretreatment step specifically includes: polishing the surface of the wedge-shaped gradient channel structure layer, and cleaning the polished wedge-shaped gradient channel structure layer and the mesh structure layer.

[0021] According to another aspect of the present invention, there is provided an application of the surface structure for enhancing condensation heat transfer, which is used for enhancing condensation in a condensation heat exchanger or a condensation end of a steam chamber or a desalination water collection system.

[0022] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:

[0023] (1) The surface structure for enhancing condensation heat transfer of the present invention combines a mesh structure layer with a wedge-shaped gradient channel structure layer. The mesh structure layer can effectively limit the overflow of condensate, so that the condensate is reasonably confined in the wedge-shaped grooves of the wedge-shaped gradient channel structure layer. At the same time, the wedge-shaped gradient channel structure promotes the downward transport process of the liquid film, so that the condensate can be quickly discharged downward in the wedge-shaped groove. These provide good support for the structural surface to achieve efficient drip-film condensation heat transfer.

[0024] (2) The present invention combines wedge-shaped fins with wedge-shaped grooves to provide an asymmetric flow channel for the condensate. The condensate droplets or liquid columns are restricted by the wall surface in the groove to form an asymmetric curvature interface at the upper and lower ends. The generated Laplace pressure difference can drive the droplets or liquid columns to move in a self-driven manner, which is beneficial to accelerate the separation of the condensate.

[0025] (3) The present invention utilizes a chemical oxidation method to oxidize the metal surface to produce a metal oxide with a nanostructure, or utilizes a coating method to deposit metal oxide nanoparticles or silicon oxide nanoparticles on the surface of the wedge-shaped gradient channel structure layer and the mesh structure layer as a nanostructure layer, providing nanoscale roughness, so that the surface hydrophobicity obtained after subsequent hydrophobic treatment is stronger, reducing the adhesion of condensate on the surface and accelerating the flow of surface condensate.

[0026] (4) The present invention uses a molecular self-assembly method to form a hydrophobic coating with a monolayer thickness by which hydrophobic molecules form chemical bonds with oxygen atoms of surface oxides, or uses a physical deposition method to attach hydrophobic organic polymers or carbon nanotubes to the surface as a hydrophobic layer; the formed hydrophobic coating ensures that droplets are formed on the mesh structure layer structure during the condensation process, and that liquid columns or discontinuous liquid films are formed in the wedge-shaped gradient channel structure, thereby avoiding the formation of a large-area continuous liquid film on the surface, thereby accelerating the renewal of the condensate and reducing the thermal resistance of the condensate.

[0027] (5) The mesh diameter of the mesh structure layer of the present invention is smaller than the channel width of the wedge-shaped gradient channel structure. The purpose is to ensure that the resistance that the condensate in the wedge-shaped gradient channel structure layer needs to overcome to pass through the mesh structure layer and overflow the channel is greater than the resistance of the condensate flowing along the channel, thereby limiting the condensate in the wedge-shaped gradient channel structure within the channel and preventing the condensate from overflowing and flooding the mesh structure layer.

[0028] (6) The mesh diameter of the mesh structure layer of the present invention is 10μm to 100μm, which is smaller than the capillary size and can reduce the droplet detachment diameter and accelerate the condensate detachment. At the same time, the size should not be too small to avoid the condensate clogging the mesh holes; the mesh wire width of the mesh structure layer is 10μm to 80μm, which size range can ensure that the mesh structure layer has good thermal conductivity and reliable strength; the width of the wedge-shaped fin structure and the wedge-shaped groove structure are independently selected from 0.2mm to 1.4mm, which is smaller than the capillary size and can limit the shape of the condensate in the channel, while ensuring that the flow resistance of the condensate is small. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The figure is a top view schematic diagram of a surface structure for enhancing condensation heat transfer according to the present invention.

[0030] Figure 2 It is a side view schematic diagram of a surface structure for enhancing condensation heat transfer according to the present invention.

[0031] Figure 3 A local SEM image of a surface structure for enhancing condensation heat transfer according to the present invention.

[0032] Figure 4 (a) is a SEM image of a copper oxide nanostructure layer formed on the surface of a copper-based wedge-shaped gradient channel of a surface structure for enhancing condensation heat transfer prepared in Example 1 of the present invention; (b) is a SEM image of a copper oxide nanostructure layer formed on a copper-based mesh structure layer.

[0033] Figure 5The figures are the condensation droplet-liquid film behavior images on the surface of the hydrophobic wedge-shaped gradient channel structure of Comparative Example 1 at different supercooling degrees, wherein (a) is a schematic diagram of the wedge-shaped gradient channel structure, (b) is the condensation droplet-liquid film behavior image when the supercooling degree is 2K, (c) is the condensation droplet-liquid film behavior image when the supercooling degree is 6K, and (d) is the condensation droplet-liquid film behavior image when the supercooling degree is 10K.

[0034] Figure 6 The images of the condensed liquid droplet-liquid film behavior on the surface of the single-layer copper mesh structure of Comparative Example 2 at different supercooling degrees are shown; wherein (a) is a schematic diagram of the single-layer copper mesh structure, (b) is an image of the condensed liquid droplet-liquid film behavior when the supercooling degree is 2K, (c) is an image of the condensed liquid droplet-liquid film behavior when the supercooling degree is 6K, and (d) is an image of the condensed liquid droplet-liquid film behavior when the supercooling degree is 10K.

[0035] Figure 7 The present invention provides an image of the behavior of condensed liquid droplets-liquid films on the surface of the wedge-shaped gradient channel-copper mesh composite structure disclosed in Example 1 of the present application; wherein (a) is a schematic diagram of the wedge-shaped gradient channel-copper mesh composite structure, (b) is an image of the behavior of condensed liquid droplets-liquid films when the supercooling degree is 2K, (c) is an image of the behavior of condensed liquid droplets-liquid films when the supercooling degree is 6K, and (d) is an image of the behavior of condensed liquid droplets-liquid films when the supercooling degree is 10K.

[0036] Figure 8 The condensation heat flux density q of the surface structure of Example 1, Comparative Example 1 and Comparative Example 2 varies with the supercooling degree ΔT.

[0037] Fig. 9 The condensation heat transfer coefficient h of the surface structure of Example 1, Comparative Example 1 and Comparative Example 2 varies with the supercooling degree ΔT.

[0038] Fig.10 The condensation heat flux density q of the surface structure of Example 1, Example 2, Example 3 and Comparative Example 2 varies with the supercooling degree ΔT.

[0039] Fig.11 The condensation heat transfer coefficient h of the surface structure of Example 1, Example 2, Example 3 and Comparative Example 2 varies with the supercooling degree ΔT.

[0040] In the figure, 100 is a mesh structure layer; 101 is a wedge-shaped gradient channel structure layer; 1002 is a nanostructure layer; 1003 is a hydrophobic coating; 1011 is a wedge-shaped fin; and 1012 is a wedge-shaped groove. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0042] According to a first aspect of the present invention, a surface structure for enhancing condensation heat transfer is provided, which comprises, from top to bottom, a mesh structure layer and a wedge-shaped gradient channel structure layer; the wedge-shaped gradient channel structure layer comprises wedge-shaped fins and wedge-shaped grooves, and the wedge-shaped fins and the wedge-shaped grooves are arranged adjacent to each other in sequence; the mesh structure layer is in contact with the wedge-shaped fins; the mesh diameter of the mesh structure layer is smaller than the channel width of the wedge-shaped gradient channel structure layer, and the surfaces of the mesh structure layer and the wedge-shaped gradient channel structure layer are both covered with a nanostructure layer, and the nanostructure layer is covered with a hydrophobic coating.

[0043] Preferably, the structure of the wedge-shaped fin is a fin structure with a wedge-shaped gradient gradually contracting, and the structure of the wedge-shaped slot is a slot structure with a wedge-shaped gradient gradually expanding.

[0044] In some embodiments, the mesh diameter of the mesh structure layer is 10 μm to 100 μm, the mesh width of the mesh structure layer is 10 μm to 80 μm, and the mesh number of the mesh structure layer is 100 to 250 meshes.

[0045] In some embodiments, the widths of the wedge-shaped fin structure and the wedge-shaped groove structure are independently selected from 0.2 mm to 1.4 mm, and the depth of the wedge-shaped groove structure is 0.2 mm to 1 mm.

[0046] In some embodiments, the material of the mesh structure layer and the wedge-shaped gradient channel structure layer is selected from copper, aluminum, and titanium.

[0047] In some embodiments, the material of the nanostructure layer is one or more of copper oxide, aluminum oxide, titanium oxide, and silicon oxide, and the material of the hydrophobic coating is one or more of thiol, fluorosilane, polytetrafluoroethylene, polydimethylsiloxane, paraffin, or carbon nanotubes.

[0048] In some embodiments, the mesh structure layer is manufactured by metal wire weaving or powder sintering.

[0049] In some embodiments, the wedge-shaped gradient channel structure layer is manufactured by machining or wire electric discharge cutting.

[0050] In some embodiments, the mesh structure layer and the wedge-shaped gradient channel structure layer are combined to form a combined body by vacuum sintering, protective gas sintering or electroplating.

[0051] According to another aspect of the present invention, a method for preparing the surface structure for enhancing condensation heat transfer is provided.

[0052] (1) making a mesh structure layer;

[0053] (2) selecting a substrate, and manufacturing a wedge-shaped gradient channel structure on the surface of the substrate to form a wedge-shaped gradient channel structure layer;

[0054] (3) covering the mesh structure layer on the wedge-shaped gradient channel of the wedge-shaped gradient channel structure layer to form a combined body;

[0055] (4) immersing the combined body in an alkaline solution or an oxidizing solution that can oxidize the surface of the combined body to form a nano-metal oxide, thereby forming a nano-structured layer on the surface of the combined body by a chemical oxidation method;

[0056] or coating a suspension of a material containing a nanostructure layer on the combined body by a coating method to form a nanostructure layer on the surface of the combined body;

[0057] (5) Immersing the combined body having the nanostructure layer in a solution containing a hydrophobic molecule precursor, and forming a hydrophobic coating on the nanostructure layer by a molecular self-assembly method or a physical deposition method.

[0058] In some embodiments, the alkaline solution is selected from a mixed aqueous solution of NaClO2, NaOH and Na3PO4, or ammonia water; the oxidizing solution is selected from an aqueous solution of H2O2, or a mixed aqueous solution of K2S2O8 and KOH, or a mixed aqueous solution of (NH4)2S2O8 and NaOH;

[0059] In some embodiments, the material of the nanostructure layer is one or more of copper oxide, aluminum oxide, titanium oxide, and silicon oxide; when the material of the nanostructure layer is copper oxide, aluminum oxide, or titanium oxide, the nanostructure layer is formed by chemical oxidation; when the material of the nanostructure layer is copper oxide, aluminum oxide, titanium oxide, or silicon oxide, the nanostructure layer is formed by coating;

[0060] In some embodiments, the material of the hydrophobic coating is one or more of thiol, fluorosilane, polytetrafluoroethylene, polydimethylsiloxane, paraffin or carbon nanotubes. When the material of the hydrophobic coating is thiol, fluorosilane or polydimethylsiloxane, the hydrophobic coating is formed by molecular self-assembly; when the material of the hydrophobic coating is polytetrafluoroethylene, paraffin or carbon nanotubes, the hydrophobic coating is formed by physical deposition.

[0061] Example 1

[0062] like Figure 1-3As shown, a surface structure for strengthening condensation heat transfer includes a mesh structure layer 100 and a wedge-shaped gradient channel structure layer 101, wherein the mesh structure layer 100 is located on the top of the wedge-shaped gradient channel structure layer 101, and the mesh structure layer 100 is used to limit the overflow of condensate. A nanostructure layer 1002 is disposed on the surface of the mesh structure layer 100 and the wedge-shaped gradient channel structure layer 101.

[0063] The wedge-shaped gradient channel structure layer 101 is provided with a wedge-shaped gradient tapered fin structure 1011 and a wedge-shaped gradient gradually expanding groove structure 1012 for promoting self-transport of the liquid film in the groove. The number of the wedge-shaped gradient tapered fin structure 1011 and the wedge-shaped gradient gradually expanding groove structure 1012 are both 17, and they are arranged at intervals to allow droplets and liquid columns to separate, forming a fast channel for the separation of droplets and liquid columns.

[0064] The upper width of the wedge-shaped fin 1011 is larger than the lower width, and the upper width of the wedge-shaped channel structure 1012 is smaller than the lower width. The upper width of the wedge-shaped fin 1011 is 1.0 mm, and the lower width is 0.4 mm. The upper width of the wedge-shaped channel 1012 is 0.4 mm, and the lower width is 1.0 mm, and it changes monotonically linearly along the length direction. The height of the wedge-shaped fin is 0.4 mm. The mesh structure layer 100 is a copper mesh with a mesh size of 150; Figure 3 SEM image of the surface structure that enhances condensation heat transfer.

[0065] A method for preparing a surface structure for enhancing condensation heat transfer comprises the following steps:

[0066] S10, using a copper mesh weaving device to weave a single-layer copper mesh, and cutting the copper mesh into a required size; importing the design drawing of the wedge-shaped gradient channel into a CNC milling machine, and processing the copper plate to form a wedge-shaped gradient channel structure.

[0067] S11 pretreatment: polishing the surface of the wedge-shaped gradient channel structure layer 101; cleaning the polished wedge-shaped gradient channel structure layer 101 and the mesh structure layer 100: using acetone, anhydrous ethanol, deionized water, dilute sulfuric acid and deionized water to clean the mesh structure layer 100 and the polished wedge-shaped gradient channel structure layer 101 in sequence. Among them, acetone is used to clean the oil stains on the surface of the mesh structure layer 100 and the wedge-shaped gradient channel structure layer 101, anhydrous ethanol is used to clean the acetone remaining on the surface of the mesh structure layer 100 and the wedge-shaped gradient channel structure layer 101, deionized water is used to clean the ethanol remaining on the surface of the mesh structure layer 100 and the wedge-shaped gradient channel structure layer 101, dilute sulfuric acid is used to remove oxides such as copper oxide on the surface of the mesh structure layer 100 and the wedge-shaped gradient channel structure layer 101, and deionized water is used to clean the residual dilute sulfuric acid; during the above cleaning process, the mesh structure layer 100 and the wedge-shaped gradient channel structure layer 101 can be immersed in the cleaning agent for 20 minutes, and the mass percentage of the dilute sulfuric acid is selected to be 5%. Through the pretreatment step, burrs, oil stains and oxides on the surfaces of the mesh structure layer 100 and the wedge-shaped gradient channel structure layer 101 are removed, so that the mesh structure layer 100 can be more tightly bonded to the surface of the wedge-shaped gradient channel structure layer 101.

[0068] S20, using a clamp to fix the mesh structure layer 100 and the wedge-shaped gradient channel structure layer 101 together to form a combination; placing the combination in a vacuum high-temperature sintering furnace for sintering to combine the mesh structure layer 100 with the surface of the wedge-shaped gradient channel structure layer 101 to form a combination of the two

[0069] S30, preparing a nanostructure layer, immersing the combination of the mesh structure layer 100 and the wedge-shaped gradient channel structure layer 101 in a mixed solution of NaClO2, NaOH, Na3PO4·12H2O, and deionized water in a mass ratio of 3.75:5:10:100 at a temperature of 90°C for 20 minutes, and oxidizing the combination with the chemical solution to prepare a nanostructure layer 1002 on the surface of the combination.

[0070] S40, cleaning the nanostructure layer, using deionized water to rinse the combination with the metal oxide nanostructure layer 1002 to remove the alkaline solution remaining on the surface of the combination;

[0071] S50, making a hydrophobic coating, immersing the conjugate in an ethanol solution of octadecyl mercaptan with a molar concentration of 0.0025 mol / L at a temperature of 70° C. for 1 hour to perform a molecular self-assembly reaction, then taking out the conjugate, and washing it with ethanol and deionized water in turn to form a hydrophobic coating 1003 on the nanostructure layer.

[0072] Figure 4As shown in (a), a layer of flaky copper oxide nanostructure is formed on the surface of the copper-based wedge-shaped gradient channel structure after alkaline chemical oxidation treatment. Figure 4 (b) shows the copper oxide nanostructure formed on the copper wire surface of the copper mesh. After chemical oxidation treatment with alkaline solution, a dense nanostructure is formed on the surface of the copper mesh and the wedge-shaped gradient channel structure below.

[0073] Example 2

[0074] The difference from Example 1 is that the mesh number of the copper mesh used is 100 mesh.

[0075] Example 3

[0076] The difference from Example 1 is that the mesh number of the copper mesh used is 200 meshes.

[0077] Comparative Example 1

[0078] A surface structure for enhancing condensation heat transfer, which is different from Example 1 in that its surface structure is only a wedge-shaped gradient channel structure layer, and the structure of the wedge-shaped gradient channel structure layer is the same as that of Example 1.

[0079] Comparative Example 2

[0080] A surface structure for enhancing condensation heat transfer, which is different from Example 1 in that its surface structure is only a single-layer copper mesh structure, and the single-layer copper mesh structure is the same as Example 1.

[0081] In order to verify the effect of the surface structure for enhancing condensation heat transfer disclosed in the embodiments of the present application on enhancing heat transfer performance, condensation was taken as an example to verify it through an experimental method, and the wedge-shaped gradient channel-copper mesh composite structure surface in Example 1 was compared with the wedge-shaped gradient channel structure surface in Comparative Example 1 and the single-layer copper mesh structure surface in Comparative Example 2.

[0082] The dynamic behavior and heat transfer performance of condensed droplets / liquid films of the wedge-shaped gradient channel-copper mesh composite structure of comparative example 1, the wedge-shaped gradient channel structure surface of comparative example 1, and the single-layer copper mesh structure surface of comparative example 2 were compared. Figure 5 The distribution of condensate under different supercooling conditions on the surface of the wedge-shaped gradient channel structure of comparative example 1. The wedge-shaped gradient channel structure has a certain promoting effect on the self-transport of condensate, but because the condensate in adjacent channels will merge with each other to form large droplets across multiple channels, the condensation heat transfer thermal resistance is greatly increased.

[0083] Figure 6 The distribution of condensate on the surface of the single-layer copper mesh structure of Comparative Example 2 under different supercooling conditions is shown in FIG. Figure 6Liquid film appears on some areas of the surface of the single-layer copper mesh structure in the figure. This is because the copper mesh surface condenses violently, and the narrow channel connecting the copper mesh and the substrate is not enough to provide sufficient drainage channels for the generated condensate. Therefore, the condensate overflows the copper mesh surface to form a strip-shaped liquid film area (see the dotted line in the figure), and the condensate flows downward along the strip-shaped liquid film area. However, the removal speed of the condensate flowing downward along the liquid film area is slow, and the strip-shaped liquid film area exists during the condensation process.

[0084] Figure 7 The distribution of condensate on the surface of the wedge-shaped gradient channel-copper mesh composite structure of Example 1 under different supercooling conditions. There is no serious condensate overflow on the surface of the wedge-shaped gradient channel-copper mesh composite structure in the figure. It is just that the condensate overflows from the copper mesh surface at the lower end where it is about to leave the surface. This is because the opening of the wedge-shaped channel at the lower end is not enough to quickly discharge the condensate, and the mesh size is appropriate, just so that the condensate overflows from the copper mesh surface at the lower part where it is about to leave the surface, achieving rapid removal. The droplets condense on the surface of the copper mesh, and the formed droplets enter the bottom of the copper mesh and are sucked into the wedge-shaped gradient gradually expanding groove, forming a thin liquid film in the groove. The groove acts as a drainage channel, and the condensate flows downward, so that the surface of the copper mesh is not covered by a large amount of liquid film.

[0085] On the surface of the wedge-shaped gradient channel-copper mesh composite structure, the steam condenses rapidly on the top of the copper mesh. The wedge-shaped groove provides a condensate removal channel to drain the condensate from the groove, so that the condensate generation and removal paths are separated, thereby achieving efficient drop-film condensation heat transfer. In addition, the surface area occupied by the overflow of the condensate on the surface of the wedge-shaped gradient channel-copper mesh composite structure is small. Under different degrees of supercooling, the proportion of the covered surface area remains basically unchanged and is much smaller than the proportion of the covered area of ​​the condensate on the surface of the wedge-shaped gradient channel structure and the surface of the single-layer copper mesh.

[0086] The above-mentioned heat transfer performance experimental results show that the copper mesh restriction layer in the enhanced condensation heat transfer surface structure disclosed in the embodiment of the present application can effectively limit the overflow of the condensate, so that the condensate is reasonably confined in the groove. At the same time, with the help of the wedge-shaped gradient expansion channel to promote the downward transport process of the liquid film, the condensate can be quickly discharged downward in the groove. In addition, the copper mesh has a good thermal conductivity coefficient and can control the heat exchange thermal resistance of the surface structure at a reasonable level, thereby realizing efficient drip film condensation heat transfer.

[0087] Figure 8 The heat flux q of the three surfaces of Example 1, Comparative Example 1 and Comparative Example 2 varies with the degree of supercooling ΔT. Figure 8It can be seen that the heat flux density on the surface of the wedge-shaped gradient channel structure and the surface of the single-layer copper mesh structure has a similar change trend with the increase of supercooling, and the heat flux density curves of the two are basically coincident when the supercooling ΔT is less than 4 K. When the supercooling further increases, the heat flux density curve of the wedge-shaped gradient channel-copper mesh composite structure surface is significantly higher than that of the other two surfaces.

[0088] Fig. 9 The heat transfer coefficient h of the three surfaces of Example 1, Comparative Example 1 and Comparative Example 2 varies with the degree of supercooling ΔT. Fig. 9 It can be seen that when ΔT = 2K and 6K, the heat transfer coefficient h of the wedge-shaped gradient channel-copper mesh composite structure surface is 87.8kW / (m 2 ·K)、63.9kW / (m 2 ·K), compared with the surface of the wedge-shaped gradient channel structure and the single-layer copper mesh surface, h increased by 51% and 86% respectively. From the above analysis of the condensate droplet-liquid film behavior, it can be seen that the droplet film condensation heat transfer performance on the surface of the wedge-shaped gradient channel-copper mesh composite structure is significantly enhanced mainly because it has a higher surface condensate removal efficiency, effectively separates the channels for condensate generation and removal, and makes the condensate reasonably restricted by the copper mesh restriction layer in the gradient gradually expanding micro-grooves and discharged downward along the grooves. The top copper mesh surface maintains efficient condensation, and there is no large-scale condensate overflow on the surface.

[0089] Fig.10 The heat flux density q of the surface structure of Example 1, Example 2, Example 3 and Comparative Example 2 varies with the degree of supercooling ΔT. Fig.10 The mesh size of the 100-mesh copper mesh is too large to effectively limit the overflow of the surface condensate, causing the surface copper mesh to be immersed in the liquid film. The pore sizes of the 150-mesh and 250-mesh copper meshes are relatively small, and both can effectively limit the overflow of the surface condensate.

[0090] Fig.11 The heat transfer coefficient h of the surface structure of Example 1, Example 2, Example 3 and Comparative Example 2 varies with the degree of supercooling ΔT. Fig.11It can be seen that the heat flux density curve on the surface of the wedge-shaped gradient channel-copper mesh composite structure (100 mesh) is located below the surface of the single-layer copper mesh. Combined with the previous analysis of the condensation droplet-liquid film behavior on these two surfaces, it can be seen that the 100-mesh copper mesh as a restricting layer cannot effectively restrict the occurrence of liquid film overflow. Adding 150-mesh and 250-mesh copper meshes on the surface of the wedge-shaped gradient micro-groove can effectively limit the occurrence of surface condensate overflow. However, compared with the surface of the wedge-shaped gradient channel-copper mesh composite structure (150 mesh), the copper mesh pore size used on the composite structure surface of the wedge-shaped gradient channel-copper mesh composite structure (250 mesh) is smaller. At a small supercooling degree (ΔT<1.6K), the copper mesh surface has a large specific surface area, more nucleation sites, and a larger heat transfer coefficient; while at a large supercooling degree (ΔT>1.6K), the narrow mesh of the 250-mesh copper mesh hinders the removal of the condensate, and the less efficient condensate removal also limits the utilization of the condensation area in the groove, resulting in a lower heat transfer coefficient on its surface than that of the wedge-shaped gradient channel-copper mesh composite structure (150 mesh).

[0091] It should be noted that the above description of the alkaline solution, chemical oxidation reaction temperature, chemical oxidation reaction time, mass percentage of dilute sulfuric acid, molar concentration of thiol, single molecule self-assembly temperature and single molecule self-assembly time is only an example in the embodiments of the present application and is not intended to be the sole limitation on the embodiments of the present application.

[0092] The preparation method of the enhanced condensation heat transfer surface structure disclosed in the embodiment of the present application has simple steps, reasonable design, easy implementation, strong operability, and is convenient for large-scale preparation and production, and has important practical value and promotion significance.

[0093] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A surface structure for enhancing condensation heat transfer, characterized in that: The invention discloses a method for manufacturing a nanostructured material for the present invention, comprising, from top to bottom, a mesh structure layer (100) and a wedge-shaped gradient channel structure layer (101); the wedge-shaped gradient channel structure layer (101) comprises wedge-shaped fins (1011) and wedge-shaped grooves (1012); the wedge-shaped fins (1011) and the wedge-shaped grooves (1012) are arranged adjacent to each other in sequence; the mesh structure layer (100) is in contact with the wedge-shaped fins (1011); the mesh diameter of the mesh structure layer (100) is smaller than the channel width of the wedge-shaped gradient channel structure layer (101); the surfaces of the mesh structure layer (100) and the wedge-shaped gradient channel structure layer (101) are both covered with a nanostructure layer (1002); and the nanostructure layer (1002) is covered with a hydrophobic coating (1003).

2. A surface structure for enhancing condensation heat transfer according to claim 1, characterized in that: The structure of the wedge-shaped fin (1011) is a fin structure with a wedge-shaped gradient gradually contracting, and the structure of the wedge-shaped groove (1012) is a groove structure with a wedge-shaped gradient gradually expanding.

3. The surface structure for enhancing condensation heat transfer according to claim 1, characterized in that: The mesh diameter of the mesh structure layer (100) is 10 μm to 100 μm, the mesh width of the mesh structure layer (100) is 10 μm to 80 μm; and the mesh number of the mesh structure layer (100) is 100 to 250 meshes.

4. The surface structure for enhancing condensation heat transfer according to claim 2, characterized in that: The widths of the wedge-shaped fin structure (1011) and the wedge-shaped groove structure (1012) are independently selected from 0.2 mm to 1.4 mm, and the depth of the wedge-shaped groove structure (1012) is 0.2 mm to 1 mm.

5. The surface structure for enhancing condensation heat transfer according to claim 1, characterized in that: The materials of the mesh structure layer (100) and the wedge-shaped gradient channel structure layer (101) are selected from copper, aluminum, and titanium.

6. The surface structure for enhancing condensation heat transfer according to claim 1, characterized in that: The material of the nanostructure layer (1002) is one or more of copper oxide, aluminum oxide, titanium oxide, and silicon oxide; the material of the hydrophobic coating (1003) is one or more of thiol, fluorosilane, polytetrafluoroethylene, polydimethylsiloxane, paraffin, or carbon nanotubes.

7. The method for preparing a surface structure for enhancing condensation heat transfer according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) making a mesh structure layer; (2) selecting a substrate, and manufacturing a wedge-shaped gradient channel structure on the surface of the substrate to form a wedge-shaped gradient channel structure layer; (3) covering the mesh structure layer on the wedge-shaped gradient channel of the wedge-shaped gradient channel structure layer to form a combined body; (4) immersing the combined body in an alkaline solution or an oxidizing solution that can oxidize the surface of the combined body to form a nano-metal oxide, thereby forming a nano-structured layer on the surface of the combined body by a chemical oxidation method; or coating a suspension of a material containing a nanostructure layer on the combined body by a coating method to form a nanostructure layer on the surface of the combined body; (5) Immersing the combined body having the nanostructure layer in a solution containing a hydrophobic molecular precursor, and forming a hydrophobic coating on the nanostructure layer by a molecular self-assembly method or a physical deposition method.

8. The method for preparing a surface structure for enhancing condensation heat transfer according to claim 7, characterized in that: The alkaline solution is selected from a mixed aqueous solution of NaClO2, NaOH and Na3PO4 or ammonia water; the oxidizing solution is selected from a H2O2 solution, a mixed aqueous solution of K2S2O8 and KOH, or a mixed aqueous solution of (NH4)2S2O8 and NaOH.

9. The method for preparing a surface structure for enhancing condensation heat transfer according to claim 7, characterized in that: Before step (3), a pretreatment step is also included, and the pretreatment step specifically includes: polishing the surface of the wedge-shaped gradient channel structure layer, and cleaning the polished wedge-shaped gradient channel structure layer and the mesh structure layer.

10. Use of a surface structure for enhancing condensation heat transfer according to any one of claims 1 to 6, characterized in that: Use it for enhanced condensation in condensing heat exchangers, at the condensing end of steam chambers or for desalination water collection.

Citation Information

Patent Citations

  • Super-hydrophobic condensation surface and preparation method thereof

    CN108571913A

  • Method for preparing carbon nanotube film reticular structure for reinforcing water vapor condensation

    CN110849167A

  • Condensation wall surface structure and heat pipe heat exchanger

    CN118882382A

  • Double-layer steam collecting structure and preparation method and application thereof

    CN119063505A

  • Method of intensification of heat exchange and device for its realization

    SU1677483A1